Role of flavonoids in controlling obesity: molecular targets and mechanisms - Mahboob, Anns; Samuel, Samson Mathews; Mohamed, Arif; Wani, Mohmmad Younus; Ghorbel, Sofiane; Miled, Nabil; Büsselberg, Dietrich; Chaari, Ali (Frontiers in Nutrition, 2023)
Obesity presents a major health challenge that increases the risk of several non-communicable illnesses, such as but not limited to diabetes, hypertension, cardiovascular diseases, musculoskeletal and neurological disorders, sleep disorders, and cancers. Accounting for nearly 8% of global deaths (4.7 million) in 2017, obesity leads to diminishing quality of life and a higher premature mortality rate among affected individuals. Although essentially dubbed as a modifiable and preventable health concern, prevention, and treatment strategies against obesity, such as calorie intake restriction and increasing calorie burning, have gained little long-term success. In this manuscript, we detail the pathophysiology of obesity as a multifactorial, oxidative stress-dependent inflammatory disease. Current anti-obesity treatment strategies, and the effect of flavonoid-based therapeutic interventions on digestion and absorption, macronutrient metabolism, inflammation and oxidative stress and gut microbiota has been evaluated. The use of several naturally occurring flavonoids to prevent and treat obesity with a long-term efficacy, is also described.